2019
DOI: 10.31229/osf.io/u29bg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Grey literature: use, creation, and citing habits of faculty researchers across disciplines (version 2; 20191107)

Abstract: INTRODUCTION Grey literature is ephemeral and the level to which it is created, used, and cited by faculty, graduate students, and other researchers is not well understood. METHODS This electronic survey was distributed to a sample (57%) of the faculty across a wide variety of disciplines with the only criteria based on tenure and tenured track faculty at the University of Minnesota - Twin Cities, a large R1 institution. RESULTS Faculty across the disciplines both use and create grey literature for several rea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Cooper et al (2019) conducted a survey on faculty across various disciplines at the University of Minnesota, Twin Cities, a large R1 institution with 18 colleges to examine their experiences with GL. Eighty-four per cent of (139) faculty members used and created GL for various reasons across/different disciplines.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Cooper et al (2019) conducted a survey on faculty across various disciplines at the University of Minnesota, Twin Cities, a large R1 institution with 18 colleges to examine their experiences with GL. Eighty-four per cent of (139) faculty members used and created GL for various reasons across/different disciplines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that librarians need to be more aware of where and how GL may be discovered. Librarians can advocate and promote the use and creation of GL among faculty in all disciplines (Cooper et al, 2019). discussed the collection development strategies for scientific GL in research libraries.…”
Section: Introductionmentioning
confidence: 99%